The Habsburg Empire under siege - Michels, Georg Bernhard, 19??- (Montreal ; London ; Chicago)
xvii, 603 sayfa
Keywords: “During the seventeenth century Hungary's diverse population of peasants, townsmen, soldiers, and county nobles rose up against the violent imposition of the Counter-Reformation, the Habsburg military occupation, and exhorbitant war taxes. In The Habsburg Empire under Siege Georg Michels explores the little-known grassroots revolts that threatened the Habsburgs' hold over the Hungarian borderlands. Based on extensive research in Hungarian, Austrian, and Dutch archives, this revisionist study shifts attention away from high politics, diplomacy, and military confrontation to the popular revolts that took place during the two decades before the 1683 siege of Vienna. Michels reveals a complex environment in which Calvinist Hungarians, Lutheran Slovaks, Lutheran Germans, and Orthodox Ukrainians worked to defend their religion against brutal Habsburg Counter-Reformation campaigns. Challenging preconceived notions of European, Middle Eastern, and East European history, this book tells a dramatic story of Reformation and Counter-Reformation violence, covering proxy wars, guerrilla warfare, refugee flight, migration from Hungary into Ottoman territory, and largely unknown Christian-Muslim encounters. Offering a trans-imperial perspective that reassesses the complex relationship between Hungarians, Habsburgs, and Ottomans, The Habsburg Empire under Siege portrays the resistance of ordinary men and women and their hopes for liberation from Habsburg oppression, reclaiming their place in history.” --